Arsenic trioxide combined with transarterial chemoembolization for unresectable primary hepatic carcinoma: A systematic review and meta-analysis. Issue 18 (May 2018) - Song, Peng; Hai, Yang; Ma, Wantong; Zhao, Longhe; Wang, Xin; Xie, Qinjian; Li, Yang; Wu, Zhengrong; Li, Yingdong; Li, Hongyu
Abstract: Background: Primary hepatic carcinoma (PHC) is the third commonest leading to cancer death around the world, and transarterial chemoembolization (TACE) has been proposed as the first-line therapeutic treatment for patients with unresectable PHC. This study aims to determine whether the combination of As2 O3 and TACE is superior to alone TACE for achieving more clinical therapeutic efficacy, survival time, life quality and safety in patients with unresectable PHC. Methods: A comprehensive literature search was conducted on the clinical controlled trials comparing therapeutic effects of As2 O3 & TACE versus alone TACE for unresectable PHC through English databases (including PubMed, Embase, and the Cochrane Library) and Chinese databases (including China Knowledge Resource Integrated Database, Wanfang Database, Weipu Database, and Chinese Biomedical Database). The last search was in 30 August 2017. A recursive search was performed with bibliographies of relevant studies. There were no language restrictions. Primary outcomes, defined a priori, were therapeutic responses (clinical effective rate and clinical benefit rate), survival time, life quality, and adverse events of As2 O3 & TACE compared with alone TACE expressed as relative risk (RR) with 95% confidence intervals (CI). Results: 25 clinical controlled trials involving 1886 participants were included. We found that there were significant superiority associated with As2 O3 & TACE compared with alone TACE in clinical benefit rate (RR: 1.24, 95% CI: 1.12–1.37), clinical effective rate (RR: 1.35, 95% CI: 1.17–1.55), 2-year survival rate (RR: 1.45, 95% CI: 1.20–1.75), and improving of KPS (RR: 1.31, 95% CI: 1.14–1.50). These associations were also observed in subgroups by intervened methods of As2 O3 and pulmonary metastasis. Notably, the pooled relative risk of retention of sodium and water was obviously raised in patients with As2 O3 & TACE therapy (RR: 16.616, 95% CI: 8.01 – 34.486). Conclusion: The superiority of adjuvant As2 O3 therapy combined with TACE in PHC individuals will outweigh alone TACE therapy, especially in PHC populations with pulmonary metastasis.